A framework for implementing TISIT model to integrate TQM with software and information technologies. (18th February 2009) - Gunasekaran, N.; Arunachalam, V.P.; Arunachalam, S.
This paper proposes a framework for implementing a model called Total Quality Management (TQM) Integrated with Software and Information Technologies (TISIT), which integrates the TQM foundations with the software and Information Technologies (IT). This framework enables the organisations to reduce or eliminate the gaps which are created due to the customer expectations and the actual deliveries. An algorithm has been designed, developed and validated with a case study on implementing TISIT. A generic framework is found and useful to improve the quality on continual basis in any organisation. The flexibility of this framework is that one could start from any stage as they like and continue the cycle of implementation.